Charlie and the Chocolate Factory Charlie and the Great Glass Elevator - Dahl, Roald (Cleveland : Findaway World, 2006)
Each of five children lucky enough to discover an entry ticket into Mr. Willy Wonka's mysterious chocolate factory takes advantage of the situation in his own way.